Kemampuan Bertahan BPR Kepemilikan Pemerintah Saat Pandemi - Sujadi Sujadi; Busaini Busaini; I Dewa Gde Bisma; I Nyoman Nugraha Ardana Putra; Nengah Sukendri (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
This research aims to explain the difference between a Rural Bank (BPR) company in the form of a Limited Liability Company (PT) and a Regional Business Enterprise (PD) in terms of profit and operational efficiency. Its means that research can help the government make decisions and direct policies related to changes in the form of business entities through the privatization process. The comparison between the two types of business entities included in the Comparative Research category and compared BPRs managed by the private sector (PT) with BPRs whose management to determined by the Regional Government (PD) or whose management is with local government intervention. Observations on Rural Banks in  West Nusa Tenggara (NTB), which had experienced the COVID-19 pandemic since early 2020. The comparison of profit and operation by yield and efficiency in doing business. Carried Efforts to make comparisons were carried out through independent t-test analysis. This study shows that regional government-owned BPRs can better survive a pandemic to generate profits and efficiency.